2020
DOI: 10.1017/s0007114520000458
|View full text |Cite
|
Sign up to set email alerts
|

The effect of postprandial glycaemia on cognitive function: a randomised crossover trial

Abstract: The effect on cognitive test scores of generating differences in postprandial glycaemia using test foods or beverages has been inconsistent. Methodological issues may account for some of the variable results requiring further investigation using strong study designs into the relationship between glycaemia and cognitive functioning. The objective of this study was to determine the effects of postprandial glycaemia on cognitive function by examining cognition after consumption of foods that differ only by the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…
Letter to the EditorThe effect of postprandial glycaemia on cognitive functionresponse to Young and BentonWe would like to thank Young and Benton for their interest in our work. With reference to our study (1) , of the 98•8 g total available carbohydrate in the trifle, 60•4 g came from the added sugars (sucrose or isomaltulose). For glycaemic index (GI) testing, in which 50 g of available carbohydrate was used, this equated to 30•6 g of the test sugars.
…”
mentioning
confidence: 93%
“…
Letter to the EditorThe effect of postprandial glycaemia on cognitive functionresponse to Young and BentonWe would like to thank Young and Benton for their interest in our work. With reference to our study (1) , of the 98•8 g total available carbohydrate in the trifle, 60•4 g came from the added sugars (sucrose or isomaltulose). For glycaemic index (GI) testing, in which 50 g of available carbohydrate was used, this equated to 30•6 g of the test sugars.
…”
mentioning
confidence: 93%
“…An obvious suggestion is that the small difference in GL played a part in the present negative findings. Additionally, there is large interpersonal variability in postprandial glucose response to the same food (8) , although this was not considered by Marchand et al (1) . Studies that have considered individual glycaemic responses have often found this factor to be important (3) .…”
mentioning
confidence: 99%
“…We read with interest the study by Marchand et al (1) who compared high and low glycaemic load (GL) trifles and found no significant effects on cognitive performance in young adults. As they suggest, this is a topic where there are inconsistencies due to differences in methodology.…”
mentioning
confidence: 99%